Efektivitas Model Think Pair Share dan Student Team Achievement Division terhadap Karakter Toleransi dalam Pembelajaran PPKn pada Siswa Kelas III Sekolah Dasar - Nurwandari, Nurwandari; Hardini, Agustina Tyas Asri (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
Cases of intolerance often occur in society, the main cause of many cases of intolerance is the differences in the community environment and the lack of tolerance character education instilled in society. Thus, this study aims to compare the two Think Pair Share (TPS) and Student Team Action Division (STAD) Learning Models on the character of tolerance in civics learning in elementary school students. In this study, researchers will conduct research with the type of quasi-experimental research (quasi experimental design). This research was conducted at SDN Kopeng 2 and SDN Kopeng 3 for class III students. Data collection techniques obtained by observation and questionnaires. The questionnaire used was first carried out the Validity Test and Normality Test and the results obtained were 24 questions declared valid. Next will be pretest and posttest. Then the data will be tested using the Normality Test, Homogeneity Test and t-test. Next is the Hypothesis Test, it is found that the significant value is <0.05. Then H0 is rejected and Ha is accepted, meaning that the character of tolerance in the Experiment Group is higher than the Control Group. This means that the character of tolerance in Grade III elementary school students is significantly higher using the Think Pair Share (TPS) Learning Model compared to using the Student Team Achievement Division (STAD) Learning Model.